THE OXYSTOMATOUS CRABS OF THE BARUNA EXPEDITION - Romimohtarto, Kasijan (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1967)
Oxystomata constitutes the smallest number of species among the Brachyura collected during the BARUNAÂ EXPEDITION. Fourteen species, among which of two the idetification is doubtful, have been studied and included in this paper. Though only few species recorded, many of them are to be more closely studied to ascertain their true position In taxonomy.